Las inscripciones diplomáticas de época visigoda y altomedieval (siglos vi a xii) - Vicente García Lobo; María Encarnación Martín López (Mélanges de la Casa de Velázquez, 2011)
Are inscriptions true documents, and as such do they possess legal force? There is no clear and unambiguous answer to so general a question. We have been classifying inscriptions in two broad groups, distinguished by the types of messages that they convey: diplomatic inscriptions and literary inscriptions. The first category includes signs that tell us of an act of a legal nature. If we accept the concept of a document in a broad sense, we can answer affirmatively, that all diplomatic inscriptions are documents. However, in order to recognise the legal value of the inscriptions we need to make new distinctions, depending on the type of document concerned.